80386: A Beginning of 32-bit Microprocessor by Intel - Sayed, Anas; Ashfaque, Shaikh Mohd (International Journal of Computer Sciences and Engineering, 2020)
We do have a general idea about the history of microprocessors. The microprocessor has evolved over the years; from the; ‘first single-chip’ microprocessor introduced by Intel-the INTEL 4004, that was a 4-bit microprocessor to the recent 64-bit microprocessors. History has it; Intel has been a leader in technology innovation. Intel has given some of the biggest contributions to the evolution of microprocessors. One such salient microprocessor introduced by Intel was the Intel 80386, which is also known as i386 or 386. 386 was the first 32-bit microprocessor launched in October 1985 that brought along the feature of virtual mode.